School Culture and the Internalization of Virtue in Free Nutritious Eating Programs (MBG): A Phenomenological Study of the Development of Civilized Behavior Among Students - Sugandi Miharja; Sarbini Sarbini; Bukhori Bukhori; Agustian Ramadana Putera; Meli Aulia Utami (Journal of Society Counseling, 2026)
The Free Nutritious Meal Program (MBG) not only serves to meet students' nutritional needs but also plays a strategic role in shaping school culture and internalizing the values of virtue. This research aims to examine the role of school culture in supporting the internalization of virtue values through the implementation of the MBG Program, as well as understanding the development of civilized behavior among students. The research uses a qualitative approach with phenomenological methods to explore the experiences and meanings of education actors, including principals, teachers, program managers, school committees, and students at the elementary, junior high, and high school levels in West Java Province. Data were collected through in-depth interviews, participatory observations, and documentation studies, then validated through triangulation of sources and techniques. Data analysis employs a phenomenological approach with stages of data reduction, theme encoding, grouping essential meanings, data presentation, and interpretation of participants' experiences. The results of the study show that the MBG Program contributes to the formation of civilized behavior through habituation, example, and strengthening of social norms that are integrated in school culture. Developed virtue values include discipline, responsibility, gratitude, social care, cleanliness, politeness, and respect for food and the environment. Practices such as praying before and after meals, queuing in an orderly manner, eating food according to portions, maintaining a clean dining area, managing waste responsibly, and teacher examples have been proven to strengthen the internalization of these values. The MBG program also encourages the development of students' cognitive, affective, psychomotor, and spiritual aspects in an integrated manner. These findings confirm that the MBG Program has the potential to be an effective means of character education through strengthening school culture and habituating virtue values in students' daily lives.